High consumption of energy-dense nutrient-poor foods among low-income groups in the Mississippi Delta and Alabama. Issue 6 (30th April 2020) - Cohen, Deborah A; Bogart, Laura M; Han, Bing; Williamson, Stephanie; Castro, Gabriela
Abstract: Objective: To assess the consumption of sugar-sweetened beverages (SSB) and other energy-dense nutrient-poor (EDNP) foods in two Southern low-income communities targeted by the Balance Calories Initiative, a campaign by the top-three American beverage companies intended to reduce the consumption of sugary beverages by 20 % over 10 years. Design: We conducted self-administered intercept surveys in front of food retail outlets between August and November 2016. We recruited adults with children <18 years living at home and adolescents aged 10–17 years with parental consent. Setting: Retail food outlets in Mississippi and Alabama, USA. Participants: Adults ( n 11 311) and adolescents ( n 3460). Results: The percentage of high SSB consumers (≥4 servings/d) was 40·9 % among adult males, 32·3 % among adult females, 43·0 % among adolescent males and 34·4 % among adolescent females (male – female difference, P < 0·0001). In aggregate, respondents also reported consuming a mean of 3 servings of salty snacks, cookies and/or candy in the past 24 h, with adolescent males reporting 4 servings. Conclusions: SSB should be a primary target of future interventions to improve dietary intake, but EDNP foods likely contribute as many daily kilojoules as SSB among this population. Future campaigns should aim to limit the consumption of all EDNP foods.